Long-term effects of an acute and systemic administration of LPS on adult neurogenesis and spatial memory - Valero, Jorge; Mastrella, Giorgia; Neiva, Ismael; Sánchez, Silvia; Malva, João O. (Frontiers in Neuroscience, 2014)
The cognitive reserve is the capacity of the brain to maintain normal performance while exposed to insults or ageing. Increasing evidences point to a role for the interaction between inflammatory conditions and cognitive reserve status during Alzheimer's disease (AD) progression. The production of new neurons along adult life can be considered as one of the components of the cognitive reserve. Interestingly, adult neurogenesis is decreased in mouse models of AD and following inflammatory processes. The aim of this work is to reveal the long-term impact of a systemic inflammatory event on memory and adult neurogenesis in wild type (WT) and triple transgenic mouse model of AD (3xTg-AD). 4 month-old mice were intraperitoneally injected once with saline or lipopolysaccharide (LPS) and their performance on spatial memory analyzed with the Morris water maze (MWM) test 7 weeks later. Our data showed that a single intraperitoneal injection with LPS has a long-term impact in the production of hippocampal neurons. Consistently, LPS-treated WT mice showed less doublecortin-positive neurons, less synaptic contacts in newborn neurons, and decreased dendritic volume and complexity. These surprising observations were accompanied with memory deficits. 3xTg-AD mice showed a decrease in new neurons in the dentate gyrus compatible with, although exacerbated, the pattern observed in WT LPS-treated mice. In 3xTg-AD mice, LPS injection did not significantly affected the production of new neurons but reduced their number of synaptic puncta and impaired memory performance, when compared to the observations made in saline-treated 3xTg-AD mice. These data indicate that LPS treatment induces a long-term impairment on hippocampal neurogenesis and memory. Our results show that acute neuroinflammatory events influence the production of new hippocampal neurons, affecting the cognitive reserve and leading to the development of memory deficits associated to Alzheimer's disease pathology.